Rural informatics engineering: towards development of e-inclusion value chain framework / Dr Wan Abdul Rahim Wan Mohd Isa, Dr Syaripah Ruzaini Syed Aris and Maslina Abdul Aziz - Wan Mohd Isa, Wan Abdul Rahim (Dr.); Syed Aris, Syaripah Ruzaini (Dr.); Abdul Aziz, Maslina (2014)
The Malaysian government has taken initiatives to promote ICT literacy and to meet future demands of knowledge society. Although the community was very much ready for the implementation of the project, capability of the governance in handling the project after delivery is questionable. Problems may occur in terms of ICT Centre, source of funding is hard to obtain, misunderstanding of the community in the project planning and implementation, change of requirements is hard to manage, and conflict of interest between the project intention with the state and national initiatives. This research attempt to overcome these issues by performing a systematic Requirements Engineering approach. Initial investigation by interview and survey to the target community will be performed to measure the community readiness. Technology Readiness and Acceptance Model will be used to measure the community readiness. The input will be used to analyse the requirement and strategize and design the e-inclusion value chain framework.